Pelatihan Bahasa Inggris Berbasis Toefl Bagi Para Guru SMP se-MGMP Bahasa Inggris Kabupaten Purworejo - Nugraeni, Ismawati Ike; WIdiyanti, Menik; Rokhayati, Titi; Widodo, Sri (Surya Abdimas, 2018)
The study aims at giving training to improve the English teachers’ skill of SMP in Purworejo Regency, especially in related to TOEFL based-test. In accordance to the aims, the method used was by giving intensif training combined with the theories, practice, and discussion. It also used the trainee’s performance (post-test) at the end of the training as the indicator of their improvement. The result of the training revealed that the TOEFL based-English training became one of the ways to improve the English teachers’ skill. The teachers can get beneficial knowledge about the underlying theory, principles, and strategies in doing TOEFL test indicated by the result of their post-test, and improvement in their general English skills. Besides, the result of the training can be applied as consideration to take schools’ policies related to their English teachers’ quality.